2017
DOI: 10.3906/biy-1605-89
|View full text |Cite
|
Sign up to set email alerts
|

Wild-growing Rosa heckeliana Tratt.: phenolic constituentswith cytotoxic and antioxidative properties

Abstract: Rosa heckeliana, as one of the wild-growing species of the family Rosacea, has a wide use in the folk medicine; however, scientifically there is very little known about it. Our objective was to examine the antioxidative and antiproliferative properties of Rosa heckeliana root extract and its phenolics. The phenolic constituents, namely catechin, caffeic acid, and ellagic acid, were obtained by the methods of extraction, fractionation, and purification through column chromatography. The DPPH and ABTS radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Simultaneously, nhexane solvents were effective for non-polar metabolites such as steroids and terpenoids 14 . However, the IC50 values shown by the three were still much lower than doxorubicin at only 0.25 μg/mL, as shown in TableII.The cytotoxic test showed that the anticancer activity of ethanol extract, ethyl acetate, and n-hexane fraction was included in the inactive category (IC50 >100 μg/mL) based on The National Cancer Institute (NCI) category16,17 . Previously, research on an ethanol extract of D. affinis on T47D cells and HeLa cells had IC50 values of 828.3 and 300.5 μg/mL, respectively 11 .…”
mentioning
confidence: 99%
“…Simultaneously, nhexane solvents were effective for non-polar metabolites such as steroids and terpenoids 14 . However, the IC50 values shown by the three were still much lower than doxorubicin at only 0.25 μg/mL, as shown in TableII.The cytotoxic test showed that the anticancer activity of ethanol extract, ethyl acetate, and n-hexane fraction was included in the inactive category (IC50 >100 μg/mL) based on The National Cancer Institute (NCI) category16,17 . Previously, research on an ethanol extract of D. affinis on T47D cells and HeLa cells had IC50 values of 828.3 and 300.5 μg/mL, respectively 11 .…”
mentioning
confidence: 99%